Unbecoming blackness : the diaspora cultures of Afro-Cuban America - López, Antonio M. (New York University Press, 2012)
In this work, the author uncovers an important, otherwise unrecognized century-long archive of literature and performance that reveals Cuban America as a space of overlapping Cuban and African diasporic experiences.